Pengintegrasian Teknologi dalam Kegiatan Need Assessment Siswa di Indonesia: A Systematic Literature Review - Wahid, Ahmad; Syukur, Yarmis; Neviyarni, Neviyarni; Putri, Kanaya Yose; Sihombing, Sri Cahaya (UIN Kiai Haji Achmad Siddiq Jember, 2025)
Need assessment activities are one of the keys to success in planning guidance and counseling services in schools. With the rapid development of technology today, researchers and practitioners are encouraged to develop various tools and media for guidance and counseling activities, including need assessment. The purpose of this research is to examine and analyze what instruments have been integrated with technology by experts to support need assessment activities. The method used in this study is a systematic literature review that applies the PRISMA standards. Literature was collected through the Scopus and Sinta Ristekbrin databases. The results of the systematic literature review indicate that several types of need assessment products integrated with technology have proven to be effective and efficient, including Potensia Apps, a computer-based need assessment instrument application, Acceptability of Mental-Health Mobile App Survey (AMMS), a management information system for problem checklist tools (DCM), a web-based DCM, Hybrid Mobile Sociometry, and an AUM PTSDL processing application (SP-AUM PTSDL Version 1). Therefore, this study recommends that researchers and practitioners apply and empirically test these products in other research locations and develop them further in order to improve them for the sake of providing quality guidance and counseling services based on student needs